Comparison of pregnancy detection methods in live white‐tailed deer - Jared F. Duquette; Jerrold L. Belant; Dean E. Beyer Jr.; Nathan J. Svoboda (Wildlife Society Bulletin)
Abstract Assessing ungulate reproduction is important to biologists for managing populations and predicting trends. We compared efficacy of trans‐abdominal ultrasound and pregnancy‐specific protein B (PSPB) white‐tailed deer (Odocoileus virginianus) pregnancy estimates, respectively, from January to mid‐April 2009–2011 in the south‐central Upper Peninsula of Michigan, USA. We observed a strong agreement (K = 0.68, SE = 0.13, 95% CI = 0.42–0.94) of PSPB and ultrasound in categorizing pregnant and nonpregnant deer. Five deer were determined to be pregnant by ultrasound but not by PSPB and 6 females were judged to be nonpregnant using either method. Total cost for PSPB testing of 101 deer was US$2,220, whereas ultrasound equipment cost US$14,150. Trans‐abdominal ultrasound and PSPB provided accurate detection of pregnancy in live white‐tailed deer. We recommend PSPB for studies testing comparatively small numbers (up to several hundred) of deer. However, we recommend ultrasonography if real‐time pregnancy determination is needed (e.g., vaginal implant transmitter use), particularly for large numbers (i.e., several hundred to thousands) of deer. © 2012 The Wildlife Society.